Manajemen Strategi Pemasaran Syariah Terhadap Peningkatan Profitabilitas Home Industry Ikan Wader Crispy - Hasan, Zainol; Humaydy, M. Idham; Albadri, Albadri (Fakultas Syariah dan Ekonomi Islam Universitas Ibrahimy, 2024)
Home Industry Crispy Fried Spotted Barb Fish is an Islamic business venture in the culinary sales sector which operates in the field of food production and provides various forms of packaging, the net of which is increasing rapidly from year to year. However, in previous years there was a decline in income due to decreasing consumer interest which of course had an impact on the business. This research uses a qualitative approach. The data source in this research is primary data obtained through interviews with the owner of this home industry, head of marketing, employees and consumers. Secondary data is records or documentation that previously existed. The results of research on sharia marketing strategy management towards increasing the profitability of the Home Industry Crispy Fried Spotted Barb Fish are that there is more emphasis on good service, friendly, polite, no lies, good to all consumers and continues to innovate so that with this strategy it can compete with food products others and regular consumers are given a discount on every purchase. If the goods that have been purchased do not match the quality of the goods, home industry will replace the goods that have already been purchased. Sales from the average period 2018–2022, in the first year 2018-2020 experienced an increase and in 2021 experienced a decrease due to the lack of catches of fresh wader fish due to frequent flooding. The biggest increase occurred in 2022 because conditions had returned to normal (no flooding) and became a supplier for shops in Bondowoso